2003
DOI: 10.1073/pnas.1631983100
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the optimum duration of antibiotic prophylaxis in an anthrax outbreak

Abstract: A critical consideration in effective and measured public health responses to an outbreak of inhalational anthrax is the optimum duration of antibiotic prophylaxis. We develop a competing-risks model to address the duration of antibiotic prophylaxis and the incubation period that accounts for the risks of spore germination and spore clearance. The model predicts the incubation period distribution, which is confirmed by empirical data. The optimum duration of antibiotic prophylaxis depends critically on the dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 25 publications
2
67
0
1
Order By: Relevance
“…However, this simple strategy has been largely nullified because germination of spore populations is heterogeneous, with some spores, often called superdormant spores, germinating extremely slowly and potentially coming back to life long after treatments are applied to inactivate germinated spores (8,9,16). The concern over superdormant spores in populations also affects decisions such as how long individuals exposed to B. anthracis spores should continue to take antibiotics, since spores could remain dormant in an individual for long periods and then germinate and cause disease (3,11).…”
mentioning
confidence: 99%
“…However, this simple strategy has been largely nullified because germination of spore populations is heterogeneous, with some spores, often called superdormant spores, germinating extremely slowly and potentially coming back to life long after treatments are applied to inactivate germinated spores (8,9,16). The concern over superdormant spores in populations also affects decisions such as how long individuals exposed to B. anthracis spores should continue to take antibiotics, since spores could remain dormant in an individual for long periods and then germinate and cause disease (3,11).…”
mentioning
confidence: 99%
“…The incubation period is defined as the time from pathogen exposure to the onset of symptoms [16,20]. Owing to factors such as host susceptibility, size of inoculum, strain virulence and chance, infected persons can experience different incubation periods.…”
Section: Incubation Periodmentioning
confidence: 99%
“…n can subsequently be estimated indirectly by using equation (3.7) with the known E and the estimate of d. This latter process can be illustrated with a fictitious example (devised for this review) in which E ¼ 1300 people who are situated inside the same building on 30 March are exposed to an aerosolized release of the causative agent of anthrax. Each person is assumed to inhale d ¼ 1000 spores, and their probability of infection is derived from a withinhost model where the inhaled spores can either germinate in the lungs of the host (resulting in infection) or be cleared by the host's defence mechanisms [16,52]. In the form of equation (3.7) with g ¼ fl, ug, this 'competing risks' model is given…”
Section: Prospective Analysis 321 Instantaneous Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Prior modeling and simulation studies have indicated that rapid response to an anthrax attack significantly reduces morbidity and mortality, with estimated effects of various strategies dependent on model parameters and timing of the response. [11][12][13][14][15] For example, Wein et al estimated that 1 kilogram of anthrax spores released upwind of 11.5 million persons would result in 123,400 deaths if the public health response began on Day 2 after an attack, but the number of deaths would more than double if the response was delayed until Day 5. 11 Other studies evaluated the comparative cost-effectiveness of various response strategies and found important advantages in responding rapidly and combining postattack vaccination with antibiotic prophylaxis for anthrax exposed victims.…”
mentioning
confidence: 99%